SKRINING SELULASE DARI TANAH HUTAN MANGROVE PANTAI SUWUNG BALI - I Nengah Wirajana; Ketut Ratnayani; Darma Asih Yuliana (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2012)
Mangrove soil has high biodiversity and well known as potential location for enzymes exploration. The aim of direct screening for cellulase of mangrove soil is to find out the cellulase activity from mangrove soil. Mangrove soils were collected from three different locations labelled as A (8o43’38.20”SL), B (8o43’46,18”SL), and C (8o43’37,38”SL). The screening was conducted by Filter Paper Assay and Carboxymethyl Cellulose Assay methods. The results showed that cellulase activities can be measured directly from mangrove soil samples of Suwung Beach-Bali. The highest cellulase activities were 0,866 U/g soil by Filter Paper Assay and4,176 ± 0,630 U/g soil by Carboxymethyl Cellulose Assay, given by soil samples C.